Chloroplast genome of Trapa bispinosa Roxb. (Trapa, Lythraceae) - Lin Lin; Jie Wang; Yu-Xue Zhao; Li Ma; Cui-Hua Gu; Zhi-Qiang Wu (Mitochondrial DNA. Part B. Resources, 2021)
Trapa bispinosa Roxb. is an annual aquatic herb with great significance of medicinal, edible and economic value. Here, we reported the complete chloroplast genome sequence of Trapa bispinosa and conducted preliminary investigation of its phylogenetic relationship with other related species. As the result showed, the whole chloroplast genome size was 155,556 bp consisting of four adjoining regions, i.e., a large/small single copy (LSC, 88,506 bp/SSC, 18,274 bp) region and two inverted repeat (IRs, 24,388 bp) regions. Among 112 identified unique genes were 78 protein coding genes, 30 transfer RNA (tRNA) genes, and four ribosomal RNA (rRNA) genes. Trapa spp. were precisely clustered as a monophyly, and simultaneously, the closest relation between Trapa bispinosa and Trapa natans were strongly supported in the maximum likelihood analysis.